2015
DOI: 10.1007/s11205-015-1185-1
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Multidimensional Poverty in Contemporary Australia

Abstract: Successfully addressing social inequalities requires moving from one-dimensional to multidimensional poverty measures, but evidence on Australia is still largely reliant on the former. Using panel data and counterfactual simulations, we examine the relative roles of material resources, employment, education, health, social support, community participation, and safety perceptions in explaining changes in multidimensional poverty in Australia between 2001 and 2012. We find that year-on-year absolute changes in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
(23 reference statements)
1
18
0
Order By: Relevance
“…Scutella et al () carried out sensitivity analysis to different choices of weights and found that this made little to no difference in the prevalence estimates. Additionally, new work by Martinez & Perales () based on a different framework of creating multi‐dimensional poverty found practically similar results to those using the framework developed by Scutella et al (). Relatedly, for small area estimation methods, the problem often encountered is whether we estimate every single component at the small area level and then composite or to simply estimate the composited result (as we have done in this application).…”
Section: Conclusion and Discussionsupporting
confidence: 56%
“…Scutella et al () carried out sensitivity analysis to different choices of weights and found that this made little to no difference in the prevalence estimates. Additionally, new work by Martinez & Perales () based on a different framework of creating multi‐dimensional poverty found practically similar results to those using the framework developed by Scutella et al (). Relatedly, for small area estimation methods, the problem often encountered is whether we estimate every single component at the small area level and then composite or to simply estimate the composited result (as we have done in this application).…”
Section: Conclusion and Discussionsupporting
confidence: 56%
“…Noble et al (2006Noble et al ( , 2010 andNoble & Wright (2013) also used Grade 7 as the threshold. 11 Disability was also included in recent local(Frame et al, 2016;Omotoso & Koch 2017) and international (e.g Suppa, 2015;Hanandita & Tampubolon, 2016;Martinez Jr & Perales, 2017). studies.http://repository.uwc.ac.za…”
mentioning
confidence: 99%
“…In order to advise on the latter, we must first understand the former. In both policy and scholarly discourse, the term ‘poverty’ has been viewed through an economic lens and has referred almost solely to income level; the oft-referred-to poverty line is relatively easy to measure and is used to compare groups both within and across countries (Martinez Jr and Perales, 2017). These poverty lines were originally based on definitions of poverty as absolute poverty, where poverty is understood as lacking sufficient income to meet basic needs (Lister, 2004).…”
Section: Definitions Of ‘Poverty’mentioning
confidence: 99%
“…Other aspects of Australian poverty research have extensively drawn on panel and administrative data in order to understand and identify trends and the prevalence of poverty. Kostenko et al (2009), for instance, used data from the Household, Income and Labour Dynamics in Australia (HILDA) survey to measure the extent of poverty and social exclusion in Australia (see also Martinez Jr and Perales, 2017; Saunders and Naidoo, 2018). Azpitarte and Bodsworth (2015) similarly used HILDA survey data to determine the socioeconomic factors that affect the likelihood of someone remaining in poverty.…”
Section: Australian Poverty Researchmentioning
confidence: 99%